Community Service Innovation: Data Updates Google Maps for UMKM Promotion and Social Facilities - Fadlilah, Fadlilah; Indriyani, Tuti; Chaniago, Fransisko; Fitriani, Suci; Badriyah, Fina; Julianti, Linda; Purnama, Boby Yasman; Summiyani, Summiyani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Community Service (PKM) with the theme “Innovations in Community Service: Updating Google Maps Data for the Promotion of UMKM and Social Facilities” is motivated by the rapid development of information technology, particularly geospatial information systems such as Google Maps, which significantly support various community activities, including spatial planning, local economic promotion, and improved access to social facilities. The purpose of this service is to update Google Maps data to support the promotion of UMKM and social facilities in the area. This activity involved youth and the general public of Dusun Eka Jaya, using methods such as lectures, discussions, and question-and-answer sessions, attended by 30 participants. The approach included providing understanding and explanation of the material, along with socialization and discussion regarding updating Google Maps data. The results showed many inaccuracies in the digital map data, such as incorrect positioning of roads and social facilities. The service team, together with the youth, made corrections and additions to the data, including UMKM locations. Consequently, the digital map became more accurate, and the community increasingly understood how to independently update data and utilize Google Maps in daily activities, including online shopping transactions. This activity provided technical, social, and economic benefits to the community of Dusun Eka Jaya, Kecamatan Dendang, Kabupaten Tanjung Jabung Timur, Province of Jambi.